2021
DOI: 10.1080/02103702.2021.1888490
|View full text |Cite
|
Sign up to set email alerts
|

Growing up in a socially bilingual environment: simultaneous acquisition of a typologically close language (Crecer en un entorno social bilingüe: adquisición de una lengua de forma simultánea a otra lengua tipológicamente similar)

Abstract: Previous research indicates that developmental contexts influence language development. These developmental contexts include bilingualism, which is the focus of the current paper. This study analyses the influence that the acquisition of a language, Catalan, has when the simultaneous acquisition of another similar language, Spanish, occurs. This influence is examined according to degree of exposure to the languages. The parents of 801 children completed the Catalan version of the MacArthur-Bates CDI-II questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The application of the MUAQ revealed that answers to basic questions about home and preferred language(s) offer limited insights into the linguistic profiles of our study population and/or sociolinguistic context, Catalonia, where there is no majority language (Serrat et al, 2021). In our study, every participant is bilingual to some extent; responses regarding their language of comfort and languages spoken at home were evenly divided between Spanish, Catalan, and both languages.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The application of the MUAQ revealed that answers to basic questions about home and preferred language(s) offer limited insights into the linguistic profiles of our study population and/or sociolinguistic context, Catalonia, where there is no majority language (Serrat et al, 2021). In our study, every participant is bilingual to some extent; responses regarding their language of comfort and languages spoken at home were evenly divided between Spanish, Catalan, and both languages.…”
Section: Discussionmentioning
confidence: 77%
“…The need for tools that measure multilingualism as a multidimensional factor becomes especially relevant in sociolinguistic situations like the one in Catalonia, the context of our study, where two official languages, Catalan, and Spanish, coexist and none of them is a minority language (Serrat et al, 2021). While Catalan is the main language of schooling, both languages are widely used, and there is virtually no monolingual Catalan population (Camus and Aparici, 2020;Tolchinsky et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As the literature suggests, exposure to vocabulary items spoken by different talkers results in faster and more accurate development than exposure to the same items spoken by a single talker (Richtsmeier et al, 2009). In the same line, Rojas et al (2016) or Serrat et al (2021) also found that preschoolers with access to input by different interlocutors show higher rates of expressive language skills, due to the wider range of topics, referents and vocabulary items that children are exposed to and, subsequently, acquire. However, an important limitation regarding the present study lies in the way sociocommunicative diversity was measured, given the fact that the question that was addressed to parents in the questionnaire might have been interpreted differently by different participants.…”
Section: Discussionmentioning
confidence: 90%
“…The pre-Covid group was created by selecting a sub-sample from the normative sample of the Catalan MB-CDI ( Serrat et al, 2022 ). To create this control group, we randomly selected those children who matched the post-Covid children in the following variables: (a) age; (b) sex; (c) prematurity status; (d) linguistic context (i.e., degree of exposure to languages other than Catalan, see Serrat et al, 2021 ); (e) birth order; and (f) education of mothers (see Table 1 for sociodemographic variables).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation